A method for calculating rock disintegration resistance index based on multiple dry-wet cycle disturbances

By using multiple dry and wet cycle disturbances in rock disintegration resistance tests, screening and calculating the proportion of particle content in each particle size group of rocks, the problem that the existing technology cannot accurately reflect the rock disintegration characteristics is solved, and a more accurate assessment of rock disintegration resistance is achieved, providing more scientific technical support for the engineering.

CN116183872BActive Publication Date: 2025-04-18SHANDONG UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310233095.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-13
Publication Date
2025-04-18
Estimated Expiration
2043-03-13

AI Technical Summary

Technical Problem

The existing rock disintegration resistance test methods cannot accurately reflect the disintegration characteristics of different rocks under the influence of multiple groundwater and excavation disturbances, resulting in the calculation results that do not conform to the actual situation of the project.

Method used

The rock disintegration resistance index calculation method based on multiple dry and wet cycle disturbances is adopted. The rock is subjected to multiple dry and wet cycles through a disintegration tester to screen the disintegration residues, calculate the proportion of particle content in each particle size group, and determine the number of disintegration cycles based on the stability of the particle proportion curve, and calculate the rock disintegration resistance index.

Benefits of technology

This method can more accurately reflect the stable state of rock disintegration and crushing degree under multiple dry and wet cycles, provide more scientific assessment of rock disintegration resistance, and provide more accurate technical support for the engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116183872B_ABST
    Figure CN116183872B_ABST
Patent Text Reader

Abstract

The present invention provides a method for calculating the rock disintegration resistance index based on multiple dry-wet cycle disturbances, and relates to the technical fields of geotechnical engineering and rock disintegration evaluation when exposed to water. The calculation method mainly includes: conducting a disintegration resistance test through a disintegration resistance tester; screening the disintegration residue according to a specified standard sieve; calculating the proportion of particles of different particle sizes in the disintegration residue and drawing a particle proportion curve of each particle size group; determining the number of disintegration cycles according to the number of times the particle proportion curve of each particle size group reaches stability; calculating the rock sample disintegration resistance index according to a given correlation coefficient; analyzing the size of the disintegration resistance index and evaluating the degree of disintegration resistance of the rock sample. The present invention makes up for the deficiency that the disintegration resistance index is the same in conventional disintegration resistance tests, but the degree of rock sample fragmentation varies greatly, and multiple dry-wet cycle disturbances are more in line with the influence of excavation and groundwater on rock disintegration resistance in actual engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of geotechnical engineering and rock disintegration evaluation when exposed to water, and in particular to a method for calculating a rock disintegration resistance index based on multiple dry-wet cycle disturbances. Background Art

[0002] In rock engineering projects such as traffic tunnel construction, hydraulic chamber excavation, and underground mining tunnel excavation, rocks are usually softened and disintegrated due to construction disturbance and the action of groundwater, which in turn causes large deformation and damage to the surrounding rock of the underground excavation chamber, and even collapse. The disintegration resistance of rock can reflect the ability of rock to resist softening and disintegration when it encounters water, and is one of the important rock characteristic parameters in geotechnical engineering. It is usually measured through disintegration resistance tests and expressed as a disintegration resistance index.

[0003] At present, the disintegration resistance test in the laboratory is usually carried out according to the geological and mining industry standard of the People's Republic of China (DZ / T 0276.9-2015). The main experimental steps are: select rock samples and record numbers; dry rock samples, cool to room temperature, weigh, and record data; install cylinders and connect motors; fill water into the water tank and control the water level; start the tester and rotate at 20r / min for 10min; dry for 24h, cool to room temperature, repeat the above steps, and then determine the rock disintegration resistance index through the test results of the second dry-wet cycle. A large number of test results show that under the same disintegration resistance index calculated by this method, the degree of disintegration and crushing of the rock in the screen drum often varies greatly. It is not in line with the actual engineering situation to quantify the degree of rock disintegration resistance only by the standard disintegration resistance index obtained after the second cycle.

[0004] In order to increase the number of cycles to improve the reliability of the test results, Chinese Patent Publication No. CN111751244A discloses a disintegration test box and test method that can be set for multiple cycles. The patent improves the test device so that the disintegration test box does not need to transfer the sample during the test, which solves the error caused by the breakage of the sample during the transfer in the disintegration test, making the test results more accurate and reliable. However, during the construction process of the project site, the rock is usually affected by groundwater and excavation many times. The number of cycles required for different rocks to completely disintegrate is not the same (greater than 2 times). The artificial setting of the number of cycles cannot accurately reflect the degree of disintegration resistance of different rocks, and also makes the operability lack of scientific basis, and it is impossible to obtain the particle size distribution of the rock sample after each disintegration cycle. As a research method, it is acceptable, but it lacks practical guidance for engineering.

[0005] In order to standardize the disintegration test and provide technical support for on-site design and construction, Chinese Patent Publication No. CN107560963B discloses a single-sided water loss disintegration test method for extremely soft rock. The single-sided disintegration depth and disintegration material grading disintegration rate calculation method can restore the extremely soft rock disintegration situation on the simulated slope site to the greatest extent and fully describe the disintegration information. This method belongs to a single-sided water immersion disintegration test and is only applicable to slope engineering. However, in underground engineering, rocks are usually affected by excavation disturbances. At the same time, the impact of groundwater on rock disintegration is all-round, not just single-sided immersion. The test method in this invention cannot well answer the characteristics of rock disintegration when encountering water during underground engineering excavation. Summary of the invention

[0006] In order to standardize the disintegration test and improve the reliability of the test results, the present invention provides a method for calculating the rock disintegration resistance index based on multiple dry-wet cycle disturbances. This calculation method needs to conform to the actual disintegration and crushing conditions of the rock sample in the sieve tube in the disintegration resistance test, and is more suitable for engineering practice.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0008] A method for calculating rock disintegration resistance index based on multiple dry-wet cycle disturbances is characterized by mainly comprising:

[0009] Step 1: Conduct a disintegration resistance test on the rock to be tested using a disintegration resistance tester;

[0010] Step 2: Sieve the disintegration residue according to the standard sieve, calculate the content ratio of particles of different particle sizes in the disintegration residue and draw the particle ratio curve of each particle size group;

[0011] Step 3: Determine the number of disintegration cycles according to the number of times the particle proportion curve of each particle size group reaches stability;

[0012] Step 4: Calculate the disintegration resistance index of the rock sample to be tested according to the evaluation coefficient of the particles in each particle size group and the particle content ratio of each particle size group;

[0013] Step 5: Analyze the size of the disintegration resistance index and evaluate the disintegration resistance of the rock to be tested.

[0014] Furthermore, the specific steps of the method for calculating the rock disintegration resistance index based on multiple dry-wet cycle disturbances of the present invention are as follows:

[0015] Step 1: Select multiple representative rock samples from the rocks to be tested, and grind each rock sample into a nearly spherical shape;

[0016] Step 2: Dry and cool the selected rock samples to room temperature, then take them out, weigh them, and record the initial data of the rock samples.

[0017] Step 3: Place all the cooled rock samples in the tester for disintegration test, and then use standard sieves with mesh sizes of 20mm, 10mm, 5mm and 2mm to sieve the rock samples. After disintegration, the particles are divided into five particle size groups: larger than 20mm, 10-20mm, 5-10mm, 2-5mm and less than 2mm. Calculate the particle content proportions of the five particle size groups, represented by D1-D5;

[0018] Step 4: Repeat step 3 to obtain the particle content ratio of five particle size groups n times;

[0019] Step 5: With the number of cycles as the horizontal axis and the percentage of particles in each particle size group obtained in each cycle as the vertical axis, a curve of the percentage of particles in each particle size after the rock sample has undergone n disintegration cycles is drawn;

[0020] Step 6: Analyze the particle proportion curves of each particle size after n disintegration cycles. When the particle content proportion of all particle size groups has no significant change compared with the previous time, that is, when the particle proportion curve reaches stability, it is recorded as the nth w times, as the number of cycles completed, the disintegration resistance test is stopped;

[0021] Step 7: Introduce the evaluation coefficient C i Calculate n using a similar weighted average method according to formula (1) w Rock disintegration resistance index after the first dry-wet cycle;

[0022]

[0023] Where:

[0024] I nw Represents the rock disintegration resistance index; D i Represents a particle size group in the nth w The particle content ratio after the first cycle; C i Represents the evaluation coefficient of a certain particle size group;

[0025] Among them: when the particle size is greater than 20mm, C1=100; when the particle size is 10-20mm, C2=50; when the particle size is 5-10mm, C3=25; when the particle size is 2-5mm, C4=10; when the particle size is less than 2mm, C5=0;

[0026] Step 8: Obtain the rock sample disintegration resistance index by formula (1), and then evaluate the disintegration resistance of the rock to be tested according to the size of the rock sample disintegration resistance index; the evaluation criteria are:

[0027] When 80≤I nw When ≤100, it indicates that the resistance of the rock to be tested to collapse is very high;

[0028] When 60≤I nw When it is less than 80, it indicates that the rock to be tested has a high degree of resistance to collapse;

[0029] When 40≤I nw When it is less than 60, it indicates that the resistance of the rock to be tested is moderate;

[0030] When 20≤I nw When it is less than 40, it indicates that the resistance to collapse of the rock to be tested is low;

[0031] When 5≤I nw When it is less than 20, it indicates that the disintegration resistance of the rock to be tested is very low;

[0032] When 0≤I nw When it is less than 5, it indicates that the resistance of the rock to be tested to collapse is extremely low.

[0033] Furthermore, during the disintegration test, the rotation speed of the sieve drum was 20 r / min, and the rotation time was 10 min.

[0034] Furthermore, in step 2, the drying temperature is 105°C to 110°C.

[0035] Furthermore, in step 1, the number of rock samples is 10, each weighing 40 to 60 g, with a total mass of 450 to 550 g.

[0036] The advantages of the present invention are:

[0037] 1. The present invention calculates the percentage of particle content in each particle size group after each dry-wet cycle, and uses this to draw a curve of the percentage of particles of each particle size after each disintegration cycle of the rock sample. The number of cycles when the curve of the percentage of particles of each particle size tends to be stable after multiple disintegration cycles is used as the number of final cycles of each rock. This is because further cycles will basically not have much impact on the degree of disintegration and crushing of the rock sample. The disintegration state obtained by the number of cycles is then used to evaluate the rock disintegration resistance index, which is more accurate. Regardless of the strength and lithology of the rock to be evaluated, the number of cycles required for complete disintegration can be found according to this method.

[0038] 2. After multiple cycles of cyclic disintegration, the disintegration and fragmentation degree of the rock sample tends to be stable. Then, the proportion of each particle size group of the rock sample in a stable state is evaluated. The evaluation coefficient is related to the particle size of the particles. Finally, the rock disintegration resistance index is calculated using the evaluation coefficient of each particle size group and the proportion of the particle content of the particle size group after the disintegration cycle. The disintegration resistance degree is judged by combining the rock disintegration resistance index with the evaluation standard, which accurately reflects the disintegration resistance degree of different rocks and provides an operational and relatively standardized method for disintegration tests. It makes up for the deficiency that the disintegration resistance index is the same but the degree of rock sample fragmentation varies greatly in conventional disintegration resistance tests, and multiple dry-wet cycle disturbances are more in line with the influence of excavation and groundwater on rock disintegration resistance in actual engineering. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Schematic diagram of the structure of the disintegration resistance tester used in the embodiment of the present invention;

[0040] Figure 2 is a flow chart of the calculation method of the present invention;

[0041] Figure 3 It is the proportion of particles of different particle sizes after each disintegration cycle of the siltstone in the embodiment of the present invention;

[0042] Figure 4 It is the proportion of particles of different particle sizes after each disintegration cycle of sandy mudstone in the embodiment of the present invention;

[0043] Figure 5 It is the proportion of particles of different particle sizes after each disintegration cycle of the red sandstone in the embodiment of the present invention;

[0044] Figure 6 It is the proportion of particles of different particle sizes after each disintegration cycle of the carbonaceous mudstone in the embodiment of the present invention.

[0045] Reference numerals

[0046] 1-control button; 2-display panel; 3-internal motor; 4-transmission shaft; 5-drum shaft; 6-screen drum; 7-water tank; 8-bottom support; 9-drum shaft support. DETAILED DESCRIPTION

[0047] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to explain the present invention, but are not used to limit the scope of the invention.

[0048] Figure 1It is a schematic diagram of the structure of the tester for the disintegration test of the present invention. This tester is a prior art. Its general structure is that a cylinder shaft support 9 and a water trough 7 are provided at the left and right ends of a bottom support 8, an upper screen cylinder 6 is arranged through the cylinder shaft support 9, the screen cylinder 6 penetrates into the water trough 7, and the screen cylinder 6 is driven by the cylinder shaft 5 and the transmission shaft 4 of the motor 3; a water trough 7 is provided between the two screen cylinders 6, and the disintegration test is performed by operating the control button 1 and the display panel 2.

[0049] Please refer to the following Figure 1-6 The present invention is described in detail with reference to the embodiments.

[0050] Figure 2 It is a flow chart of the calculation method of the present invention. As can be seen from the flow chart, the technical solution of the present invention as a whole includes the five steps S1-S5 shown in the figure. The specific operation steps are as follows:

[0051] Step 1: Select 10 representative samples of siltstone, sandy mudstone, red sandstone and carbonaceous mudstone, 40-60g each, with a total mass of 450-550g. Grind each rock sample into a nearly spherical shape and record the rock name in Table 1.

[0052] Step 2: Place the selected rock samples into the sieve drum 6 respectively, and then place the sieve drum 6 into the oven, adjust the temperature to 105℃~110℃, and dry for 24h. After drying, take out the sieve drum 6 and place it in the dryer, and take it out after cooling to room temperature. Weigh and record the initial data of the four rock samples.

[0053] Step 3: Place the cooled sieve drum 6 into the water tank 7 , connect the drum shaft 5 of the sieve drum 6 to the transmission shaft 4 , and connect it to the motor 3 .

[0054] Step 4: Add pure water into the water tank 7 and control the water level to be 20 mm below the cylinder axis 5.

[0055] Step 5: Turn on the control button 1, start the tester, and rotate the sieve drum 6 at a speed of 20 r / min for 10 minutes.

[0056] Step 6: Take out the sieve cylinder 6, and then put the sieve cylinder 6 into the oven, adjust the temperature to 105℃~110℃, and the time is 24h. After drying, take out the sieve cylinder 6 and place it in the dryer. Take it out after cooling to room temperature. Dry the disintegrated material, and use standard sieves with mesh sizes of 20mm, 10mm, 5mm and 2mm to sieve the rock sample. After disintegration, the particles are divided into five particle size groups: larger than 20mm, 10~20mm, 5~10mm, 2~5mm and less than 2mm. Calculate the particle content proportion of each particle size group, which are represented by D1~D5 in turn, and record the first data

[0057] Step 7: Repeat steps 3 to 6. After each cycle, calculate the particle content ratio of each particle size group. Then, use the number of cycles as the horizontal axis and the particle content ratio of each particle size group after each cycle as the vertical axis to draw the particle content ratio curve of each particle size after multiple disintegration cycles. When the particle content ratio curves of the five particle size groups are stable, it means that the system after rock disintegration tends to be stable and there will not be much change if it continues. At this time, the cycle ends. Figures 3 to 6 As shown, the particle proportion curve of siltstone reaches stability after the 7th dry-wet cycle, and the particle proportion curve of red sandstone reaches stability after the 9th dry-wet cycle; the particle proportion curves of sandy mudstone and carbonaceous mudstone reach stability after the 8th dry-wet cycle. The particle content proportions of each particle size group at the time of stability are recorded separately, D1~D5, see Rock Score Record Table 1.

[0058] Step 8: Evaluate the disintegration of the rock samples after the 7th dry-wet cycle of siltstone, the 9th dry-wet cycle of red sandstone, and the 8th dry-wet cycle of sandy mudstone and carbonaceous mudstone. i : When the particle size is greater than 20 mm, C1 = 100; when the particle size is 10-20 mm, C2 = 50; when the particle size is 5-10 mm, C3 = 25; when the particle size is 2-5 mm, C4 = 10; when the particle size is less than 2 mm, C5 = 0. The disintegration resistance index of the four rock samples is calculated according to formula (1).

[0059]

[0060] Step 9: The disintegration resistance index of the four types of rocks is calculated by formula (1). According to the disintegration resistance index conclusion given in Table 1, it is found that the disintegration resistance index of siltstone, sandy mudstone, red sandstone and carbonaceous mudstone is gradually reduced, and the lower the disintegration resistance index, the easier it is to disintegrate, and the lower the ability to resist disintegration. Based on this principle, the conclusion drawn from the test results of the present invention is that the resistance to disintegration of the four types of rocks is from strong to weak, siltstone> sandy mudstone> red sandstone> carbonaceous mudstone, which is consistent with the actual situation.

[0061] Table 2 is a reference table for evaluating the degree of rock disintegration resistance of the present invention. By comparing the disintegration resistance indexes of the four rocks obtained above with Table 2, it can be found that the siltstone has a very high degree of disintegration resistance, the sandy mudstone has a low degree of disintegration resistance, the red sandstone has a very low degree of disintegration resistance, and the carbonaceous mudstone sample has an extremely low degree of disintegration resistance.

[0062] It can be seen from the comparison results of the embodiments that the anti-disintegration capabilities of the four types of rocks evaluated based on the disintegration resistance index and the disintegration resistance degree are consistent and consistent with reality.

[0063] In order to verify the feasibility of the method of the present invention, the existing method is used to evaluate the disintegration resistance of the siltstone, sandy mudstone, red sandstone and carbonaceous mudstone samples involved in the present invention.

[0064] The existing industry standard (DZ / T 0276.9-2015) uses the test results of the second dry-wet cycle to determine the rock disintegration resistance index. The standard disintegration resistance index is calculated according to formula (2), and the calculation result is retained to one decimal place. The standard disintegration resistance index of the four types of rocks is recorded in Table 3.

[0065]

[0066] Where:

[0067] I d2 —— rock standard disintegration resistance index;

[0068] m r2 ——Drying mass of residual sample after rock circulation, g;

[0069] m d ——Drying mass of original sample, g.

[0070] As can be seen from Table 3, the results obtained using the existing industry standard (DZ / T 0276.9-2015) show that the disintegration resistance index of siltstone and sandy mudstone samples are very close, and the disintegration resistance index of red sandstone and carbonaceous mudstone samples are almost the same.

[0071] Table 4 is a reference table of rock disintegration resistance related to the existing calculation method. Comparing the disintegration resistance index obtained in Table 3 with Table 4, it can be found that the disintegration resistance of siltstone and sandy mudstone samples is the same and belongs to extremely high, while the disintegration resistance of red sandstone and carbonaceous mudstone is the same and belongs to low disintegration resistance. Figures 3 to 6 From the particle size ratio curve, it can be found that the disintegration and crushing degree of sandy mudstone samples is significantly higher than that of siltstone, and siltstone basically does not disintegrate; the crushing degree of carbonaceous mudstone and red sandstone is obviously inconsistent. The particle size distribution of red sandstone after disintegration and crushing is relatively uniform, while the carbonaceous mudstone is severely broken and mostly concentrated in the 2-5mm particle size group. The results calculated by existing technology are obviously inconsistent with the actual situation.

[0072] The above description is only a preferred specific implementation manner of the present invention, and is not a limitation on the implementation manner of the present application. However, the protection scope of the present invention is not limited thereto. For any technician familiar with the technical field, other different forms of changes or modifications can be made on the basis of the above description. All obvious changes or modifications derived from the technical solution of the present application are still within the protection scope of the present application.

[0073] Table 1

[0074]

[0075] Table 2

[0076]

[0077] Table 3

[0078]

[0079] Table 4

[0080]

Claims

1. A method for calculating the rock disintegration resistance index based on multiple dry-wet cycle disturbances, characterized in that: The detailed steps are as follows: Step 1: Select multiple representative rock samples from the rocks to be tested, and grind each rock sample into a nearly spherical shape; Step 2: Dry and cool the selected rock samples to room temperature, take them out, weigh them, and record the initial data of the rock samples; Step 3: Place all the cooled rock samples in a disintegration resistance tester for a disintegration test, and then use standard sieves with mesh sizes of 20 mm, 10 mm, 5 mm and 2 mm to sieve the rock samples. After disintegration, the particles are divided into five particle size groups: larger than 20 mm, 10-20 mm, 5-10 mm, 2-5 mm and less than 2 mm. Calculate the particle content proportions of the five particle size groups, expressed as D1-D5; Step 4: Repeat step 3 to obtain the particle content ratio of five particle size groups n times; Step 5: With the number of cycles as the horizontal axis and the percentage of particles in each particle size group obtained in each cycle as the vertical axis, a curve of the percentage of particles in each particle size after the rock sample has undergone n disintegration cycles is drawn; Step 6: Analyze the particle proportion curves of each particle size after n disintegration cycles. When the particle content proportion of all particle size groups has no significant change compared with the previous time, that is, when the particle proportion curve reaches stability, it is recorded as the nth w times, as the number of cycles completed, the disintegration resistance test is stopped; Step 7: Introduce the evaluation coefficient C i , using a similar weighted average method according to formula (1) to calculate n w Rock disintegration resistance index after the first dry-wet cycle; Where: I nw Represents the rock disintegration resistance index; D i Represents a particle size group in the nth w The particle content ratio after the first cycle; C i Represents the evaluation coefficient of a certain particle size group; Among them: when the particle size is greater than 20mm, C1=100; when the particle size is 10-20mm, C2=50; when the particle size is 5-10mm, C3=25; when the particle size is 2-5mm, C4=10; when the particle size is less than 2mm, C5=0; Step 8: Obtain the rock sample disintegration resistance index by formula (1), and then evaluate the disintegration resistance of the rock to be tested according to the size of the rock sample disintegration resistance index; the evaluation criteria are: When 80≤I nw When ≤100, it indicates that the resistance of the rock to be tested to collapse is very high; When 60≤I nw When it is less than 80, it indicates that the rock to be tested has a high degree of resistance to collapse; When 40≤I nw When it is less than 60, it indicates that the resistance of the rock to be tested is moderate; When 20≤I nw When it is less than 40, it indicates that the resistance to collapse of the rock to be tested is low; When 5≤I nw When it is less than 20, it indicates that the disintegration resistance of the rock to be tested is very low; When 0≤I nw When it is less than 5, it indicates that the resistance of the rock to be tested to collapse is extremely low.

2. The method for calculating the rock disintegration resistance index based on multiple dry-wet cycle disturbances according to claim 1, characterized in that: In step 3, the screen drum speed of the disintegration resistance tester is 20 r / min, and the rotation time is 10 min.

3. The method for calculating the rock disintegration resistance index based on multiple dry-wet cycle disturbances according to claim 1, characterized in that: The drying temperature in step 2 is 105°C to 110°C.

4. The method for calculating the rock disintegration resistance index based on multiple dry-wet cycle disturbances according to claim 1, characterized in that: In step 1, there are 10 rock samples, each weighing 40 to 60 g, with a total mass of 450 to 550 g.

Citation Information

Patent Citations

  • A test method for one-sided dehydration and disintegration of extremely soft rock

    CN107560963B

  • Multi-time automatic circulation disintegration-resistant test box and test method

    CN111751244A